EFEKTIVITAS PELAKSANAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERKOTAAN DI KELURAHAN RANOTANA KOTA MANADO - Kolondam, Gersonom Salomo; Ruru, Joorie Marhaen; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: The problems of poverty are quite complex requiring the intervention of all parties together and coordinated. To improve the effectiveness of poverty reduction and job creation, the government launched the National Program for Community Empowerment (PNPM's) began in 2007. The method used in this research is descriptive method with qualitative approach. A qualitative approach is used because researchers are planners, the interpreter of data / information, and in the end as well as a reporter research. This research was conducted in the village Ranotana Sario Manado District of focusing research on the effectiveness of the implementation of the National Program for Community Empowerment Urban. PNPM Mandiri is a national program to reduce poverty, especially that based on community empowerment. To improve the effectiveness of poverty reduction and job creation, the government launched the National Program for Community Empowerment began in 2007. The problems of poverty are quite complex requiring the intervention of all parties together and coordinated. To improve the effectiveness of poverty reduction and job creation, the government launched the National Program for Community Empowerment (PNPM) began in 2007. The method used in this research is descriptive method with qualitative approach. A qualitative approach is used because researchers are planners, the interpreter of data / information, and in the end as well as a reporter research. Based on the results of research and discussion, it can be concluded that the implementation of the National Program for Community Empowerment in Urban Village District of Sario Manado Ranotana not effectively be seen from the output or the amount issued results, level of satisfaction, creative products and intensity. In the determination of the action plan should involve not only the general public and government officials LKM village so that it can fit the needs of the community. Â  Keywords: The effectiveness of the implementation of the national program of community empowerment, poverty.